Appropriate Surgical Timing of Salter Innominate Osteotomy for Residual Acetabular Dysplasia in Children. Issue 10 (30th November 2022) - Sawamura, Kenta; Kitoh, Hiroshi; Kaneko, Hiroshi; Kitamura, Akiko; Hattori, Tadashi
Abstract : Background: Salter innominate osteotomy (SIO) provides favorable results for treating residual acetabular dysplasia in young children. In this study, we examined the midterm results of SIO according to the age at surgery to determine the optimal timing of this procedure. Methods: We retrospectively examined 50 hips of 42 patients (8 boys and 34 girls) with acetabular dysplasia who underwent SIO and were followed up until skeletal maturity. The center-edge angle (CEA) was measured based on the anteroposterior radiographs of the hip obtained before surgery, 5 weeks after surgery, and at the latest follow-up. Severin classification was evaluated at the latest follow-up. Patients were categorized into 3 groups according to age at surgery: younger than 7 years of age (group A), 7 to 8 years of age (group B), and 9 years of age or older (group C). Results: The mean preoperative CEA level of 0.9 degrees improved to 17.1 degrees postoperatively, which was increased to 28.1 degrees at the latest examination. Overall, 45 hips (90%) were classified as Severin I or II, with 96% in group A, 94% in group B, and 57% in group C. In group C, postoperative acetabular coverage was similar to that in the other groups (16.6 degrees in group A, 14.8 degrees in group B, and 18.1 degrees in group C), although the final outcome was unsatisfactory. The average improvement in CEA from postoperative to skeletal maturity was significantly smaller in group C than in the other groups (12.7 degrees in group A, 11.3 degrees in group B, and 3.0 degrees in group C). Conclusions: SIO showed favorable outcomes with satisfactory acetabular coverage at skeletal maturity. However, satisfactory acetabular coverage could not be obtained in some older patients because of limited postoperative remodeling capacity and smaller secondary improvement of CEA. We recommend that SIO should be performed in patients aged 8 years or younger. Level of Evidence: Level III—retrospective comparative study.